Integral assessment of lipoperoxidation processes in women with ovarian hyperandrogenism - L. I. Kolesnikova; O. V. Krusko; L. V. Belenkaya; L. V. Sholokhov; L. A. Grebenkina; N. A. Kurashova; S. I. Kolesnikov (Бюллетень сибирской медицины, 2021)
Aim. To assess the state of the ‘lipid peroxidation – antioxidant defense’ system using an integral indicator (coefficient of oxidative stress) in women with ovarian hyperandrogenism in various periods of reproductive age.Materials and methods. During an annual preventive medical examination at the Scientific Сentre for Family Health and Human Reproduction Problems, 92 women of reproductive age (18–45 years old) were divided into a group of women with polycystic ovary syndrome (PCOS) (n = 47) and a control group of healthy women (n = 45). The group of women with PCOS was further divided into subgroups according to age characteristics: the 1st subgroup consisted of women with PCOS of early reproductive age (18–35 years old), and the 2nd group had women with PCOS of late reproductive age (35–45 years old). Practically healthy women of the corresponding ages  made up the 3rd and 4th control subgroups. Standard methods were used  to study the LPO–antioxidant defense system. The oxidative stress severity was assessed by an integral indicator: the coefficient of oxidative stress.Results. An increase in ketodiens and coupled trienes serum levels, a decrease in reduced glutathione, α-tocopherol and retinol levels, and an increase in SOD activity in PCOS women of reproductive age (18–45 years old) were detected in comparison with the control group. Early reproductive age PCOS women also demonstrated an increase in oxidized glutathione and retinol concentration decrease. In the late reproductive age group of PCOS women, an increased superoxide dismutase activity was registered. The integral indicator of oxidative stress in the main group of women with PCOS was 2.5, which shows the enhancement of oxidative processes, and imbalance in the LPO–antioxidant defense system. This indicator was the most pronounced (2.8) in early reproductive age women. In women of late reproductive age, this indicator was equal to 1.9.Conclusion. The obtained data indicate the development of oxidative stress  in women with ovarian hyperandrogenism, which is mоre pronounced in the  group of late reproductive age women.